2014
DOI: 10.1080/0972060x.2014.935041
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Extraction by Hydrodistillation of Sage (Salvia officinalisL.) Essential Oil Using Water Solutions of Non-ionic Surfactants

Abstract: The extraction of Salvia officinalis L. essential oil was carried out by hydrodistillation using aqueous solutions of non ionic surfactants with different hydrophile-lipophile balance. An increase of oil yield with increasing the surfactant hydrophilic-lipophilic balance was observed. The best yield, 1.83 %, was obtained in presence of Tween 20, while the use of Span 80 did not affect the oil yield and its composition. The analysis by CG-MS and GC of essential oils obtained with and without surfactant, allowed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Hydrodistillation is a popular method used for the preparation of essential oils. However, hydrodistillation with excipients is not widely used-we have found just three studies applying this method so far [19][20][21]. Therefore, we have applied magnesium aluminometasilicate in hydrodistillation as the new excipient and have tested its effects on the nutmeg essential oil yield and its composition [22].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrodistillation is a popular method used for the preparation of essential oils. However, hydrodistillation with excipients is not widely used-we have found just three studies applying this method so far [19][20][21]. Therefore, we have applied magnesium aluminometasilicate in hydrodistillation as the new excipient and have tested its effects on the nutmeg essential oil yield and its composition [22].…”
Section: Introductionmentioning
confidence: 99%
“…Using sea water, the yield of oil-bearing rose increased statistically insignificantly by 0.045%, but the sea water significantly decreases the citronellol rate from 41.49% to 33.56%, and significantly increases geraniol (from 17.58% to 27.44%) [22]. Using non-ionic surfactants for extraction of sage essential oil it was found that Tween 20 increased the yield of oil at 1.83% and Span 80 or Span 20 had no effect [23]. Using 5% NaCl salt solution for hydrodistillation, the yield of lavender oil was 5.01 ± 0.45% in comparison with only water, where the yield was 4.55 ± 0.14% [14].…”
Section: Discussionmentioning
confidence: 99%
“…In different sources, hydrodistillation is carried out for various times and solid:solvent ratios. Hydrodistillation is carried out using water, and few studies have been carried out using extra material for extraction such as sea water [22], non-ionic surfactants [23] or 5% NaCl salt solution. [14].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, solvent extraction, hydrodistillation/steam distillation, supercritical fluid extraction (SFE), and microwave‐assisted extraction (MAE) have been widely considered for the extraction of nonvolatile compounds ( e.g . fatty oil or phenolic compounds) 4,10‐18 . In particular, hydrodistillation is deemed one of the more economic methods to produce essential oils with high purity 4,10‐13 .…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the extraction yield and kinetics of essential oils could be enhanced in such a surfactant‐assisted hydrodistillation process. For example, the extraction yield of Salvia officinalis L. essential oil by hydrodistillation was enhanced in presence of Tween 20, a common nonionic surfactant that is also known as polysorbate 20 14 . Briefly, the extraction yield was increased from 1.5% to 1.8% with Tween 20, in contrast to a trivial effect with the use of hydrophobic Span 80 nonionic surfactant.…”
Section: Introductionmentioning
confidence: 99%